Exploring the Experiences and Support of Nurses as Second Victims After Patient Safety Events in China: A Mixed-Method Approach - Tang W; Xie Y; Yan Q; Teng Y; Yu L; Wei L; Li J; Chen Y; Huang X; Yang S; Jia K (Dove Medical Press, 2024)
Wenzhen Tang,1 Yuanxi Xie,1 Qingfeng Yan,2 Yanjuan Teng,1 Li Yu,1 Liuying Wei,3 Jinmei Li,4 Yuhui Chen,1 Xiaolin Huang,1 Shaoli Yang,1 Kui Jia1 1The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People's Republic of China; 2The Sanming Second Hospital, Sanming, Fujian Province, 366099, People's Republic of China; 3Nanning Fourth People's Hospital, Nanning, Guangxi Zhuang Autonomous Region, 530021, People's Republic of China; 4Wanxiu District Chengnan Community Health Service Center, Wuzhou, Guangxi Zhuang Autonomous Region, 543000, People's Republic of ChinaCorrespondence: Kui Jia, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People's Republic of China, Email 1960728884@qq.comAim: To investigate the current status of experience and support of nurses as second victims and explore its related factors in nurses.Design: A sequential, explanatory, mixed-method study was applied.Methods: A total of 406 nurses from seven tertiary hospitals in China were chosen as participants between September to October 2023. The Chinese version of the Second Victim Experience and Support Questionnaire (SVEST), Somatic Complaints of Sub-health Status Questionnaire (SCSSQ) and Generalized Anxiety Disorder (GAD-7) were applied to collect quantitative data. Eight nurses were selected for a qualitative study through in-depth interviews. Through interpretive phenomenological analysis, the interview data were analysed to explore the experience and support of nurses as second victims.Results: Practice distress (15.74 ±  4.97) and psychological distress (15.48 ±  3.74) were the highest dimensions, indicating Chinese nurses experienced second victim-related practice and psychological distress. Nurses with different gender, age, education, marital status, income, working hours, professional titles, and unit types have different levels of second victim-related experience and support (p